2010
DOI: 10.3109/02699206.2010.503007
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and acoustic reliability estimates for the Speech Disorders Classification System (SDCS)

Abstract: A companion paper describes three extensions to a classification system for pediatric speech sound disorders termed the Speech Disorders Classification System (SDCS). The SDCS uses perceptual and acoustic data reduction methods to obtain information on a speaker's speech, prosody, and voice. The present paper provides reliability estimates for the two perceptual methods (narrow phonetic transcription; prosody-voice coding) and the acoustic analysis methods the SDCS uses to describe and classify a speaker's spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…An inter-rater agreement of 87% and 91% for accuracy of speech production and motor-speechmovement-parameters respectively, was achieved. These agreement values are within the range deemed " acceptable " for research needs (Shriberg, Fourakis, Hall, Karlsson, Lohmeier, McSweeney, et al, 2010).…”
Section: Reliability and Fi Delitysupporting
confidence: 61%
“…An inter-rater agreement of 87% and 91% for accuracy of speech production and motor-speechmovement-parameters respectively, was achieved. These agreement values are within the range deemed " acceptable " for research needs (Shriberg, Fourakis, Hall, Karlsson, Lohmeier, McSweeney, et al, 2010).…”
Section: Reliability and Fi Delitysupporting
confidence: 61%
“…The absolute magnitudes of these intrajudge and interjudge reliability estimates are not high, but they are consistent with point-by-point agreement percentages reported for other perceptually based independent and dependent variables in speech development and SSD research (e.g., Shriberg & Lof, 1991;Shriberg et al, 2010b). Tilkens et al (2017) included a summary of findings from a study series to identify acoustic correlates of abrupt inappropriate pauses.…”
Section: Reliability Estimates For the Pmmentioning
confidence: 68%
“…All data reduction and analyses are completed in the PEPPER (Programs to Examine Phonetic and Phonologic Evaluation Records; Shriberg et al, 2010a) environment. Shriberg et al (2010b) reported findings from a series of reliability estimates for each of the transcription, prosody-voice coding, and acoustic data reduction methods. As described in Part II, PM scores and scores for two of the three SPMS signs (slow articulatory rate, inappropriate sentential stress) are obtained from eligible utterances from the MSAP's continuous speech sample.…”
Section: Operationalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 includes findings for four measures of the precision and stability of participants' articulation during continuous speech that are presumed to quantify transcoding deficits. The first variable in Table 5, termed the PSI, includes 32 signs of precision and stability assessed using a system of narrow phonetic diacritics (Shriberg & Kent, 2013) and procedures for acoustic analyses (Shriberg et al, 2010a(Shriberg et al, , 2010b. As described briefly in PM I and in more detail elsewhere , the PSI was developed as a measure to identify and quantify the MSD in Figure 1 termed MSD-Not Otherwise Specified.…”
Section: Transcoding Processes In Casmentioning
confidence: 99%